Monogenic hypercholesterolemia in South Africans : familial hypercholesterolemia in Indians and familial defective apolipoprotein B-100 - Rubinsztein, David Chaim (Division of Medical Biochemistry and Structural Biology, 2018)
LDL-receptor mutations and familial defective apolipoprotein B-100 (codon 3500) (FOB), the known causes of monogenic hypercholesterolemia (MH), have similar clinical features. The nature of the mutations responsible for MH in South Africans of Indian origin was previously unknown. Similarly, the mutations in the LDL-receptor gene of a South African Black FH homozygote had also not been characterised. The aim of this thesis was to identify and analyse the LDL-receptor mutations in the Indian homozygotes NS, D, AV and AA and in the Black homozygote JL. In addition, the possible importance of FOB as a cause of MH in South Africans was also assessed. The patient NS was characterized as having two "Null" LDL-receptor alleles. His skin fibroblasts expressed no detectable LDL-receptor protein and very low levels of LDL-receptor mRNA of approximately normal size. Since NS' s LDLreceptor promoter sequence was normal, his alleles are likely to harbour exonic point mutations or minor rearrangements that cause premature stop codons. The patient D was found to be a heteroallelic homozygote. Two new point mutations in the LDL receptor, Asp₆₉ -Tyr and Glu₁₁₉-Lys, were identified. D's fibroblasts expressed about 30% of the normal surf ace complement of receptors that bound LDL poorly. This low number could at least be partially explained by their decreased stability. These mutations were not identified in any other Indian FH or hypercholesterolemic patients. Patients AV and AA were both shown to be homoallelic homozygotes for the Pro₆₆₄ -Leu mutation. This mutation was identified in 4 unrelated Muslim families of Gujerati origin suggesting that the mutation arose from this area in India. Contrary to previous reports (Knight et al. 1990, Soutar et al. 1989), neither LOL nor β-VLDL binding were shown to be affected by this mutation. These mutant receptors were rapidly degraded. Thus the disease FH in these subjects is presumably due to the low steady-state level of mature receptors that are functionally normal but exhibit accelerated turnover. The Pedi FH homozygote, JL, expressed very few LOL receptors due to decreased receptor synthesis associated with low mRNA levels and not due to enhanced degradation. One of JL's LOL receptor alleles has a 3 b.p. deletion in repeat 1 of the promoter (G. Zuilani, H. Hobbs and L.F. de Waal, personal communication). The nature of the defect in his other allele is unknown. The importance of FOB as a cause of monogenic hypercholesterolemia in the South African Indian, "Coloured" and Afrikaner populations was determined by screening hypercholesterolemic subjects with or without xanthomata. The absence of FOB in such patients, in whom the relevant common or founder South African mutations were excluded, suggested that this disorder was rarer in these groups than in North America and Europe. FOB was identified in two different families of mixed British and Afrikaner ancestry. One family contained individuals who were heterozygous for the FOB mutation, as well as the FH Afrikaner-1 and the FH Afrikaner-2 LOL-receptor mutations. In addition, 4 compound heterozygotes, who had both FOB and the FH Afrikaner-1 mutation and one individual whu inherited all 3 defects, were identified. This family allowed us to characterise the compound heterozygotes with one mutant LOLreceptor allele and FOB as having a condition that was probably intermediate in severity between the FH heterozygote and homozygote states.